The Effects of Profitability, Liquidity, Leverage, and the Pandemic on Financial Distress - Ditio Adi Surya Wijaya Hadi; Muhammad Miqdad; Siti Maria Wardayati (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2023)
This study was conducted to obtain empirical evidence on the effect of profitability, liquidity, leverage, and the COVID-19 pandemic on financial distress. This study refers to the object of research in the form of cyclical consumer sector companies listed on the Indonesian stock exchange from 2018 to 2020. The sample used in this study amounted to 35 companies with predetermined sample criteria. The analytical method used in this study is multiple linear regression analysis using the SPSS version 25 application. In this study, it was found that profitability and pandemic have an effect on financial distress, while liquidity and leverage have no effect on financial distress conditions. The results of this study are expected to be useful for interested parties to find out things that have an impact on financial distress.